Reanalysis on Performance of Microwave Phase Detector for Multisignals - Jing Deng; Hongxun Wang; Xin Xiang (Sensors)
Microwave phase detectors (MPDs) are key components of instantaneous frequency measurement (IFM) receivers and phase interferometer direction finding (PIF-DF) receivers. In conventional analyses, there is seldom a major quantitative discussion of MPD characterization when multiple signals arrive at the same time, which is often the case in complex and noisy electromagnetic environments. We have reanalyzed the characteristics of MPDs with respect to filter effects acting on more than two RF signals and differential amplifiers, which are not considered in conventional analyses. First, a step-by-step mathematical model of the signal flow is developed, which creates a cross term between the two signals and naturally introduces intermodulation effects. Second, the new response characteristics of the MPD are evaluated by simulation. Finally, the intermodulation effects of zero-forcing and extreme-forcing were found simultaneously in the crosspoint frequency and near-frequency regions of multiple signals, which led to significant deviations and errors in the output of the MPD. This effect may have significant implications for IFM and PIF-DF receivers.